Lang, J. M. (2016). Small teaching. Everyday lessons from the science of learning. San Francisco: Jossey-Bass. (Journal of Applied Learning and Teaching, 2018)
James Lang’s Small Teaching is one of my favourite books on teaching and learning in Higher Education. The activities described in the book are very appealing to me as they can be applied to multiple settings, from lecture theatres through all sorts of ‘blended learning’ all the way to a fully-online environment. Importantly, they are ‘small’, i.e. easy-to-prepare and not-so-time-consuming techniques, and they may be able to improve the effectiveness of one’s teaching without engaging in a major review – not someday, but Monday.